Gambaran Komplikasi Otitis Media Supuratif Kronis Tipe Bahaya di RSUP Dr. M. Djamil Padang Tahun 2017-2019 - Lucinda Patesia Amada Rumadas; Jacky Munilson; Dian Pertiwi (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Atticoantral type of Chronic Suppurative Otitis Media (CSOM) becomes a major health problem in developing countries. This condition has potential to be hard becaused complications that occur. Objective. This objectives of this study was to decribe atticoantral type complications CSOM at Dr M Djamil Hospital Padang years 2017-2019. Methode: This was a descriptive study using secondary data from medical record of patients diagnosed with atticoantral type CSOM at Dr M Djamil Hospital Padang periode 2017-2019. This study involved outpatients and inpatient with total subject 242 who qualify inclusion criteria. Sampling technic used total sampling technic Results. There are 242 cases atticoantral CSOM with the most age group years ˃10-20 and more men than woman. The Incidence of complications was founded to be 9,1% with the most intracranial complications age group years ˃20-30, while the most age group in intratemporal complications were years ˃10-20 and more experienced by men than women. Mortality rate was found 9,1% in intrakranial complications and no cases mortality rate in intratemporal complication. Conclusion. The incidence of compliations CSOM atticoantral type in RSUP Dr M Djamil still quite high.